El derecho a la educación en el Perú en tiempos neoliberales - Molinero Nano, Vanetty (2009)
This article attempts to make a reflection about the right to education in Peru, in order to draw some mechanisms to secure, protect and promote this right from the state and civil society. In this way, the analysis begins from an historic perspective, to demonstrate that human rights are social constructions. Then, Peruvian legislation referred to the right to education is reviewed, showing how the conceptualization of this right is transformed with the neoliberal context. Afterwards, the analysis is concluded by identifying the strifes that have been developed with the aim of guarantying the right to education in Peru.